2021
DOI: 10.1590/0034-7167-2020-0762
|View full text |Cite
|
Sign up to set email alerts
|

Child behavior during the social distancing in the COVID-19 pandemic

Abstract: Objective: To describe the daily activities performed by children from 6 to 12 years of age incomplete and analyze children’s behavior during social distancing in the face of the COVID-19 pandemic. Methods: Cross-sectional study with children in a learning stage living in Brazil. The data were collected via online form. Fisher’s exact test was applied to analyze the association of categorical variables with child behavior; when significant, it was used the odds ratio. It was considered results considered stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
13

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
0
7
1
13
Order By: Relevance
“…The closing of schools and the restriction related to COVID-19 and the curfew had detrimental effects on quality of life and physical well-being. It was reported that the anxiety rate was 1.37 times higher in children who had limited physical activity than physically active peers (Paiva, Silva, & Machado et al, 2021). In our study, even though general anxiety levels were high for all participants; Coronavirus Anxiety Scale did not result in high scores.…”
Section: Descriptive Statisticscontrasting
confidence: 66%
See 2 more Smart Citations
“…The closing of schools and the restriction related to COVID-19 and the curfew had detrimental effects on quality of life and physical well-being. It was reported that the anxiety rate was 1.37 times higher in children who had limited physical activity than physically active peers (Paiva, Silva, & Machado et al, 2021). In our study, even though general anxiety levels were high for all participants; Coronavirus Anxiety Scale did not result in high scores.…”
Section: Descriptive Statisticscontrasting
confidence: 66%
“…While the pandemic-related anxiety and detrimental effects on child development are predictable, there is not enough study on children who use hearing aids that shows this relationship clearly (Paiva, Silva, & Machado et al, 2021). This current study was conducted to make this connection noticed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…O fato da criança brincar, irá utilizar o corpo e sua imaginação, proporcionando que a mesma experiencie ações que lhes conferirão desenvolver estruturas sociais, motoras e cognitivas que poderão utilizar para todo e qualquer tipo de aprendizagem, além de promover interações com seus pares (AZEVEDO; MORAIS, 2023). Em uma pesquisa realizada no Brasil, observou-se que crianças que não realizam atividades físicas tem 1,37 vezes mais chance de terem ansiedade (PAIVA et al, 2021).…”
Section: Discussionunclassified